Probabilistic Basis of Parametrized Relativistic Quantum Theory in Curved Spacetime - John R. Fanchi (Mathematics)
A probabilistic basis for Parametrized Relativistic Quantum Theory (PRQT) has been developed for multicomponent eigenvectors and many-body applications in flat spacetime. This paper presents an extension of the multicomponent, many-body PRQT formalism to curved spacetime.